Requirements and possible simplifications for multi-ionic transport models – Case of concrete subjected to wetting-drying cycles in marine environment. (10th March 2018) - Soive, Anthony; Tran, Van Quan; Baroghel-Bouny, Véronique
Highlights: A physically and chemically based model was used to simulate chloride ingress. The use of precipitation/dissolution kinetics is essential. "Intrinsic" permeability value do not play a significant role on the chloride ingress. Boundary layer thickness that reflects the evaporation kinetics is not important. Simulations carried out in saturated conditions provide good results. Results have to be further discussed for higher "intrinsic" permeability values. Simulations with different wetting drying cycles frequencies have to be performed. Abstract: In this paper, a physically and chemically based model, which describes coupled ion-moisture transport, is used to simulate chloride ingress in concrete elements subjected to wetting-drying cycles in marine environment. Various assumptions are tested, in order to quantify the influence of taking into account dissolution/precipitation kinetics or to underline the differences between complex model and very simple one assuming saturated conditions in the latter case. Numerical simulations are compared to experimental chloride concentration profiles. Experimental data were obtained on OPC concrete (w/c = 0.43) specimens exposed to 6 h/6 h seawater wetting-drying cycles in lab (where RH and T are controlled). The results show that when the initial amounts of hydration products are known, the assessment of the chloride binding parameters is not needed. In addition, including reaction kinetics in the model is essential and improves the predictions compared to a pure thermodynamical approach. Moreover, according to sensitivity analysis the boundary layer thickness that reflects the evaporation kinetics and the "intrinsic" permeability are not important parameters for the studied concrete. Updating at each time step the transport properties in order to account for dissolution/ precipitation of mineral species does not change very much the chloride content profiles as well. Furthermore, simulations carried out in saturated conditions provide similar results to those obtained when accounting for wetting-drying cycles for the studied concrete. Then, it may be possible to use a simpler model (ie saturated conditions), and thus avoid the problematic assessment of the "intrinsic" permeability, to predict the service life of a RC structure cast with the concrete studied.